2022
DOI: 10.1007/s12015-021-10323-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Single and Repeated Dosing of Anti-Inflammatory Human Umbilical Cord Mesenchymal Stromal Cells in a Mouse Model of Polymicrobial Sepsis

Abstract: Summary Mesenchymal stromal cells (MSCs) ameliorate pre-clinical sepsis and sepsis-associated acute kidney injury (SA-AKI) but clinical trials of single-dose MSCs have not indicated robust efficacy. This study investigated immunomodulatory effects of a novel MSC product (CD362-selected human umbilical cord-derived MSCs [hUC-MSCs]) in mouse endotoxemia and polymicrobial sepsis models. Initially, mice received intra-peritoneal (i.p.) lipopolysaccharide (LPS) followed by single i.p. doses of hUC-MSC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Endotoxemia reactions are induced in BALB/c mice as previously described with minor adjustment by LPS (Sigma) ( 25 ). All mice were randomly divided into 3 groups: without MSC group, Ctrl-MSC group and SM-MSC group.…”
Section: Methodsmentioning
confidence: 99%
“…Endotoxemia reactions are induced in BALB/c mice as previously described with minor adjustment by LPS (Sigma) ( 25 ). All mice were randomly divided into 3 groups: without MSC group, Ctrl-MSC group and SM-MSC group.…”
Section: Methodsmentioning
confidence: 99%
“…A gene expression analysis also showed that after rats with LF were treated by MSC-EVs and MSCs, the expression levels of collagenases (e.g., MMP13 and MMP9), anti-inflammatory cytokines (e.g., IL-10 and TGF-β1), and antiapoptotic genes (e.g., BCL-2) were all upregulated, while the expression levels of proapoptotic genes (BAX), proinflammatory cytokines (e.g., TNF-α, IL-2), and the main factors contributing to fibrosis (Collα, α-SMA, and TIMP1) were downregulated. It was suggested that MSC-EVs could regulate the hepatic inflammatory microenvironment through the downregulation of immune cell infiltration and the regulation of both the expression and secretion of inflammatory factors, including anti-inflammatory and proinflammatory factors [3,39]. Other EVs from various sources of MSCs have shown similar effects on liver protection and regeneration, including BMSCs [40][41][42], human menstrual blood-derived MSCs [43], adipose-derived MSCs, and human liverderived MSCs [44,45] (Figure 1).…”
Section: Progress Of Mesenchymal Stem Cells In Lf Treatmentmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs), a group of unique cells, have shown great potential for unlimited self-renewal [1]. They are found in various tissues, including the liver, bone marrow, intestine, connective tissues, spleen, and placenta [2,3]. MSCs can not only differentiate into mesenchymal cell lines (e.g., osteocytes, chondrocytes, skeletal muscle cells) but also develop into ectodermal and endodermal cells (e.g., hepatocytes and neurons) [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1A presents a schematic of the timeline and the different treatments. The cell dose was selected based on a prior report of MSC treatment in mouse models (15). The mortality and weights were assessed daily for the next 3 days.…”
Section: In Vivo Experimental Designmentioning
confidence: 99%